(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we introduced the concepts of local fractional integral and generalized Mittag-Leffler kernel. Based on these, we establish Hermite-Hadamard integral inequalities and Ostrowski integral inequalities via exponentially s-preconvex functions and s-preconvex functions with generalized Mittag-Leffler kernel.